Editorial Alpha Centauri - DIAZ DUMONT, JORGE RAFAEL (Alpha Centauri, 2021)
The Alpha Centauri Scientific and Technological Research Journal is a refereed journal produced internationally, it is published QUARTERLY in the online version ISSN: 2709-4502.Alpha Centauri publishes scientific articles specializing in Applied Social Sciences and Social Sciences in Information Technology with great international impact. We are currently in trend in more than 24 countries disseminating Open Access scientific knowledge.IMAGES: Still images, audio recordings, video and related computer files for non-commercial use. NASA content (images, audio, video, and computer files used in rendering three-dimensional models, such as texture maps and polygon data in any format).